ANALYSIS OF COGNITIVE ASSESSMENT INSTRUMENTS IN GENERAL BIOLOGY LEARNING MEDIA - Trio Ageng Prayitno; Nuril Hidayati (Jurnal Pelita Pendidikan, 2022)
The existence of cognitive assessments in learning media that does not require much consideration for their feasibility as a measuring tool is one of the problems that arise because it can cause misinformation obtained by the teacher. The purpose of this study was to determine the construct validity and content of the cognitive assessment instrument and the validity of the questions, the reliability of the questions, the distinguishing power of the questions, and the level of difficulty of the questions on the cognitive assessment instruments to be used in general biology learning media. The research method used is descriptive quantitative through a survey involving one expert and 58 students of the Biology Education study program of IKIP Budi Utomo. The research limitation is a cognitive assessment of microbiology material in general biology courses. The type of instrument analyzed is a test. The results obtained are that the cognitive assessment instrument has a valid level of validity from the aspect of construct and content, the validity of the questions in the valid category, the reliability of the questions is moderate, the discriminatory power of the questions is good, and the level of difficulty of the questions is moderate. The conclusion is that the cognitive assessment instrument is appropriate to be used as an appropriate measuring tool for microbiology material in general biology learning media.